2006
DOI: 10.1080/10400435.2006.10131913
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Word Completion and Word Prediction on Typing Rates Using On-Screen Keyboards

Abstract: Word prediction is often recommended by therapists as a means to improve typing speed for clients with physical limitations. Although literature suggests that word prediction does have an effect on writing proficiency, increased speed is not one of its benefits when used with a standard keyboard. One reason given for the failure of word prediction to accelerate typing is that the user must look away from any source document to scan the prediction list during typing. Looking away from the source document may sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 7 publications
3
31
0
1
Order By: Relevance
“…This increase in cognitive load is consistent with our previous findings as well as other researchers [14,16,8,1]. The decrease in input rate due to word prediction is explained by an increasing reliance on the prediction system.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This increase in cognitive load is consistent with our previous findings as well as other researchers [14,16,8,1]. The decrease in input rate due to word prediction is explained by an increasing reliance on the prediction system.…”
Section: Discussionsupporting
confidence: 82%
“…This method relies on statistics generated from a training corpus -in our case the Switchboard Corpus, which consisted of approximately 2.6 million words. 1 Thus the probability of a particular word being predicted depends on the number of times in the training corpus that that word followed the two words the user has just typed.…”
Section: Advanced Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closer examination of the literature suggests that the different effects of word prediction found may be related to the user population and/or the type of system it is coupled with. Studies in nondisabled subjects have found improvements of approximately 3 wpm when using word prediction with on-screen keyboards but not with standard keyboards [22,34]. Word prediction did not, however, appear to be effective in nondisabled subjects using a scanning system [24].…”
Section: Effect Of Word Predictionmentioning
confidence: 99%
“…Although word prediction is used in AAC devices, researchers have questioned whether it actually increases communication rate (Venkatagiri, 1993;Koester and Levine, 1997;Anson et al, 2004). These works note the additional cognitive demands and cost of using word prediction in conjunction with a letter-by-letter interface, such as the need to shift the focus of attention to the prediction list, the time to scan the prediction list, and the cognitive effort required for making decisions about the predicted words.…”
Section: Introductionmentioning
confidence: 99%